(untitled) (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2026)
Generation Alpha, as individuals raised entirely within a digital ecosystem, is particularly susceptible to mental health disturbances resulting from non-empathic communication in digital spaces. However, the majority of school counselors in Indonesia have yet to develop adequate competencies in empathic digital communication, digital counseling, and Social Emotional Learning (SEL) tailored to the distinctive characteristics of Generation Alpha. This community service program aimed to enhance the empathic digital communication competencies of school counselors within the Guidance and Counseling Teachers’ Forum (MGBK) of Maros Regency through an integrated training program combining digital counseling and SEL approaches. The program was conducted on April 22, 2026, at a public junior high school in Maros Regency, involving 15 school counselors as participants. A participatory training method was employed, encompassing lectures, group discussions, simulations, and role-play activities. Data were collected using pretest and posttest instruments comprising 18 Likert-scale items measuring three core aspects: knowledge, attitude, and skills. The results demonstrated a meaningful improvement across all participants, with pretest scores previously distributed within the low and moderate categories shifting entirely to the high and very high categories following the training. These findings confirm that the integrated training program effectively strengthened school counselors’ empathic digital communication competencies. Furthermore, this program produced a practical training model that MGBK can adopt as a reference framework for reinforcing empathic and responsive digital counseling services in addressing the needs of Generation Alpha students.